(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
In the current sense, phytochemicals/natural products are gaining a lot of popularity as potential therapeutic agents. India, which has a long history of such preparations, needs to be assessed as potent products. Explant culture system is a process that is adaptive, repeatable, and capable of simulating in situ conditions while maintaining a sufficiently high degree of tissue integration. Using liver explants cultures, researchers tested the antioxidant activity of test compounds, namely standard aqueous (4212) and aqueous-methanolic (4308) extracts of Tecoma stans. The dose-response maxima of extracts (0.2–10 g/mL) were calculated over a 48-hour span using a mouse liver explants culture system. Key oxidative protection parameters, such as superoxide-dismutase (SOD), catalase, reduced glutathione (GSH), and malondialdehyde, were used to evaluate the antioxidant properties of extracts (MDA). The results showed that the cultured tissue’s cellular architecture was well conserved in the first 6 hours, accompanied by a steady display of specific changes over the next 24 hours. MDA levels in experimental groups increased significantly, suggesting oxidative stress induction in explants. A dosage of 2.0 g/mL extracts provided statistically significant (P 0.05) oxidative stress safety. When extract treated explants were compared to control, MDA levels, a measure of lipid peroxidation, were significantly (P 0.01) reduced by 50%. With no improvement in GSH levels, this effect was followed by a 50% rise in the first defensive enzymes SOD (50%) and catalase (18%). The study illustrates the benefit of an "explants culture method," which not only eliminates the use of nonclinical/animal models but is also simple and responsive. The current study’s findings also indicate that the aqueous-methanolic extract of Tecoma stans has higher antioxidant activity than the typical water extract.